2016
DOI: 10.1590/s0100-736x2016000800003
|View full text |Cite
|
Sign up to set email alerts
|

Laminar lesions in horses with systemic oxidative stress, committed by experimentally induced or naturally occurring gastrointestinal disorders

Abstract: Laminitis in horses can be associated with lesions in multiple organs secondary to sepsis. Twenty-one horses suffering from gastrointestinal disorders were used in the experiment; 7 horses with experimentally induced endotoxemia and intestinal ischaemia, and 14 horses suffering from naturally occurring colic syndrome. Tissue samples of lungs, liver, heart, brain, cerebellum and hoof laminar tissue were collected for histopathological and oxidative stress evaluation using nitrotyrosine and superoxide dismutase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…The marked increases in AST activity and total bilirubin concentrations in nonsurviving horses with colic can also be indicative of liver dysfunction, although the role of hemoconcentration should not be overlooked. Although total bilirubin in the horse could be affected by short‐term fasting, hepatic tissue damage is probable according to previous studies that showed the role of systemic oxidative stress in inducing tissue damage and organ failure in horses with GI disorders, rats, and mice with sepsis. Based on the present results and the abovementioned studies, it seems that tissue damage and organ dysfunction in horses with colic is likely multifactorial.…”
Section: Discussionmentioning
confidence: 98%
“…The marked increases in AST activity and total bilirubin concentrations in nonsurviving horses with colic can also be indicative of liver dysfunction, although the role of hemoconcentration should not be overlooked. Although total bilirubin in the horse could be affected by short‐term fasting, hepatic tissue damage is probable according to previous studies that showed the role of systemic oxidative stress in inducing tissue damage and organ failure in horses with GI disorders, rats, and mice with sepsis. Based on the present results and the abovementioned studies, it seems that tissue damage and organ dysfunction in horses with colic is likely multifactorial.…”
Section: Discussionmentioning
confidence: 98%
“…Araújo e colaboradores (1995) observaram correlação positiva entre os níveis de VLDL e LDL em humanos e a produção de espécies reativas de oxigênio, resultando no aumento da peroxidação lipídica e consequentemente do estresse oxidativo. O estresse oxidativo foi associado ao desencadeamento de diferentes enfermidades em equinos, tais como a obstrução recorrente de vias aéreas, a hemorragia pulmonar induzida por exercício e a laminite (LYKKESFELDT;SVENDSEN, 2007;LASKOSKI et al, 2016) mas não se conhece a relação da hiperlipidemia com o estresse oxidativo em equinos.…”
Section: Introductionunclassified